2016
DOI: 10.1002/pits.21919
|View full text |Cite
|
Sign up to set email alerts
|

Examining Potential Bias in Screening Measures for Middle School Students by Special Education and Low Socioeconomic Status Subgroups

Abstract: To provide timely and effective supports for students reading below grade level, schools require methods for quickly and accurately identifying those students in need. One method for identifying those students is through universal screening. Assessments such as oral reading fluency (ORF) and Maze reading comprehension are commonly used as screening assessments in middle grades. The current study examined ORF and Maze for evidence of bias across two subgroups known to be at increased risk for failure in reading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 28 publications
2
10
2
Order By: Relevance
“…As in previous research conducted in different states (Espin et al, 2010; Shin, 2017; Silberglitt et al, 2006; Ticha et al, 2009; Yeo, 2010), scores on the fall and spring CBMs shared strong positive unique relationships with scores on a statewide reading assessment. In contrast to some previous findings, however (Shin, 2017; Stevenson et al, 2016), CBM validity did not vary by student characteristics. These findings, if replicated, suggest that the benefit of more frequent measurement of reading skills afforded by CBMs may not be limited to the primary grades.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…As in previous research conducted in different states (Espin et al, 2010; Shin, 2017; Silberglitt et al, 2006; Ticha et al, 2009; Yeo, 2010), scores on the fall and spring CBMs shared strong positive unique relationships with scores on a statewide reading assessment. In contrast to some previous findings, however (Shin, 2017; Stevenson et al, 2016), CBM validity did not vary by student characteristics. These findings, if replicated, suggest that the benefit of more frequent measurement of reading skills afforded by CBMs may not be limited to the primary grades.…”
Section: Discussioncontrasting
confidence: 99%
“…In another recent study, meal and disability status were examined as moderators of the relationship between ORF and maze on state test performance. Findings indicated that ORF was a better predictor of state test performance for eighth-grade students without disabilities than for students with disabilities (Stevenson et al, 2016).…”
Section: Student Characteristics and Reading Cbmmentioning
confidence: 99%
See 2 more Smart Citations
“…There are limited research studies that analyzed multiassessments to identify approaches (Compton, Fuchs, Fuchs, & Bryant, 2006; O’Connor & Jenkins, 1999), but they tended to focus on screening of early elementary school–aged students. Several studies were found that examined the screening accuracy of tools for upper elementary school students on a high-stakes assessment (Baker et al, 2015; Decker, Hixon, Shaw, & Johnson, 2014; Denton et al, 2011; McGlinchey & Hixon, 2004; Nese, Park, Alonzo, & Tindal, 2011; Shapiro, Solari, & Petscher, 2008; Stevenson, Reed, & Tighe, 2016). Only one study was found that explored a multigate approach (Klingbeil, Nelson, Van Norman, & Birr, 2017).…”
Section: Purposementioning
confidence: 99%